AB0439 Clinical remission following treatment with tumour necrosis factor-alpha antagonists is not accompanied by changes in asymmetric dimethylarginine in patients with rheumatoid arthritis. (23rd January 2014) - Dimitroulas, T.; Sandoo, A.; Toms, T.; Veldhuijzen van Zanten, J.J.; Smith, J.; Kitas, G.
Abstract : Background: Rheumatoid arthritis is characterised by impaired endothelial function which contributes to increased cardiovascular morbidity and mortality. Modern therapies such as tumour necrosis factor alpha antagonists appear to reduce cardiovascular risk in this population. Asymmetric dimethylarginine (ADMA) is an endogenous competitive inhibitor of nitric oxide synthase and contributes to endothelial dysfunction. Objectives: The aim of the present longitudinal study was to investigate the effects anti-tumour necrosis factor alpha medications on serum concentrations of ADMA following 12 weeks of treatment in patients with rheumatoid arthritis. Methods: Thirty-five patients (age (mean ± SD) 55±15 years, 21 women) who qualified for anti-TNFα therapy were included in the study. Disease activity score 28 and health assessment questionnaire were performed in all patients prior to starting anti-tumour necrosis factor alpha treatment, and 2 weeks and 3 months after initiation of treatment. ADMA was measured by ELISA at the same time points. Repeated measures ANOVA and LSD post hoc analyses were used to analyse changes in ADMA levels. Results: Anti-tumour necrosis factor alpha therapy significantly reduced ESR (p<0.03), CRP (p<0.00), disease activity score 28 (p<0.00) and health assessment questionnaire (p<0.00). ADMA levels did not change significantly following 2 weeks or 3 months treatment with tumour necrosis factor alpha inhibitors. Changes in ADMA levels were not associated with changes in disease activity at 2 weeks and at 3 months. Conclusions: Reduction in inflammation after treatment with tumor necrosis factor alpha antagonists does not affect ADMA levels in patients with rheumatoid arthritis. References: Turiel M, Atzeni F, Tomasoni L, de Portu S, Delfino L, Bodini BD, Longhi M, Sitia S, Bianchi M, Ferrario P, Doria A, De Gennaro Colonna V, Sarzi-Puttini P. Non invasive assessment of coronary flow reserve and ADMA levels: a case-control study of early rheumatoid arthritis patients. Rheumatology 2009;48:834-839. A, Veldhuijzen van Zanten JJ, Metsios GS, Carroll D, Kitas GD. Vascular function and morphology in rheumatoid arthritis: a systematic review. Rheumatology (Oxford). 2011 Nov;50(11):2125-39. Disclosure of Interest: None Declared